Transcutaneous electrogastrography in patients with ileus. Relations to interleukin-1beta, interleukin-6, procalcitonin and C-reactive protein - Fraško, Roman; Maruna, Pavel; Gürlich, Robert; Trča, Stanislav (European surgical research, 2008)
BACKGROUND: The aim of the prospective study was to characterize the disturbance of gastric electrical control activity in different types of ileus and to correlate surface electrogastrography (EGG) findings with a set of inflammatory markers. PATIENTS AND METHODS: Fifty-four adult patients with mechanic, vascular and paralytic ileus proven on clinical and radiological exams and 14 age- and sex-matched controls were examined. Gastric myoelectrical activity was recorded using 3 Ag-AgCl disposable skin electrodes connected in pseudo-unipolar mode by Microdigitrapper device. The captured signal was amplified and digitalized. The dominant frequency was calculated using computerized algorithms (Fast Fourier transform and running spectrum analysis). The results were correlated with the known pathological diagnoses and 4 inflammatory parameters--interleukin (IL)-1beta, IL-6, procalcitonin (PCT) and C-reactive protein. RESULTS: Irregular EGG activity without a dominant frequency or bradygastria (electrical control activity frequency <2.4 cycles/min) was seen in all patients with both vascular and parayltic ileus and in 67.86% of the patients with obstructive ileus. Normogastria (2.4-3.7 cycles/min) was found in 32.14% of the patients with obstructive ileus. Among the patients with obstructive ileus and bradygastria, higher concentrations of IL-6 (642.0 +/- 214.7 ng/l) and PCT (0.93 +/- 0.22 microg/l) were observed compared with the patients with normogastria--IL-6 (354.5 +/- 109.2 ng/l), PCT (0.69 +/- 0.11 microg/l); p < 0.05 for both. The C-reactive protein concentration did not differ in both subgroups on p < 0.05. CONCLUSIONS: EGG examination confirmed a high sensitivity in the evaluation of gastric electrical control activity in both vascular and paralytic ileus. Significant correlation of EGG findings and both IL-6 and PCT plasma levels supports a role of the inflammatory milieu in the pathogenesis of impaired gastric electrical activity in patients with ileus.
Keywords: financování organizované; dospělí; Protein Precursors; Female; biologické markery; C-Reactive Protein; elektrodiagnostika; Biomarkers; Adult; ženské pohlaví; Calcitonin; lidé; Sensitivity and Specificity; ileus; Interleukin-6; senzitivita a specificita; proteinové prekurzory; Financing, Organized; Electrodiagnosis; Electrodes; prospektivní studie; Interleukin-1beta; Male; Aged; Prospective Studies; interleukin-6; Ileus; interleukin-1beta; transkutánní elektrická neurostimulace; elektrody; C-reaktivní protein; kalcitonin; senioři; mužské pohlaví; lidé středního věku; Transcutaneous Electric Nerve Stimulation; Middle Aged; Humans